Dogman : grime and punishment - Pilkey, Dav. 1966-; Garibaldi, Jose (New York, NY : Graphix, an imprint of Scholastic, 2020)
"When Dog Man gets fired by the mayor, he needs his friends' help to combat a new threat"
Ages 7 and up.
Keywords: Graphic novels; Dogs -- Fiction; Cats -- Fiction; Humorous stories